Peran Pendamping Program Keluarga Harapan (PKH) dalam Menurunkan Angka Stunting pada Keluarga Penerima Manfaat di Kecamatan Suliki dan Kecamatan Guguak Kabupaten Lima Puluh Kota - Susridawati R; Helmi Ali (Jurnal Mirai Management, 2023)
The research focuses on stunting cases in Suliki Sub-District and its proximity to Guguak Sub-District in Lima Puluh Kota District. The study employs qualitative analysis with purposive sampling, gathering data through observation, interviews, and documentation, followed by data reduction and analysis. Findings reveal: (1) Stunting rates development from 2020-2022. Suliki District's stunting cases remained at 12.73% in 2020-2021 but increased to 13.77% in 2022. Guguak District experienced a decrease from 3.85% (2020) to 3.38% (2021) and further to 3.11% (2022). (2) The PKH facilitators play vital roles in reducing stunting rates: a) Facilitators provide services and support, b) Mediators navigate conflicts and community needs, c) Advocates promote child nutrition and hygiene, d) Coordinators collaborate with local stakeholders for program success. (3) Stunting and non-stunting beneficiaries in both districts generally have lower education levels and engage in various livelihoods, with farming dominating. Monthly incomes range from IDR 1,500,000-1,800,000, with no significant income or employment differences between stunting and non-stunting beneficiaries. Keywords: Role, Facilitator PKH, Stunting, Beneficiary Families